INFLAMMATORY-DESTRUCTIVE PROCESS IN PERIODONTIUM WHILE MODELLING HYPО- AND HYPERREACTIVITY OF THE ORGANISM - Yu.Yu. Yarov (Український стоматологічний альманах)
The issues of clarifying the key mechanisms of development and course of generalized periodontitis in different conditions of reactivity of the organism remain relevant. The aim of the research is study of the peculiarities of course of the inflammatory-destructive process in the periodontium according to the dynamics of clinical and paraclinical indicators depending on the state of reactivity of the body in the conditions of modeling hyper- and hyporeaction.